The Combination of Electrocoagulation and Enhanced Electrooxidation for the Treatment of Petrochemical Wastewater: Biodegradability Studies - Feizi, Rouzhan; Kashani, Mohammad Rez Khavari; Jaafarzadeh, Nematollah; Varank, Gamze; Bazipur, Fatemeh; Ghanbari, Farshid (SPRINGER INT PUBL AG, 2023)
In this study, electrocoagulation (EC) followed by enhanced electrooxidation (EO) was harnessed to treat a real petrochemical wastewater (PWW). In EC process, two kinds of aluminum and iron electrodes were used and under optimal condition (200 mA applied current) COD removal was achieved 42% and 38% for Al and Fe electrodes, respectively. Combined treatment methods of EO/UV, EO/US, and EO/Fe(II) were assessed in comparison with single EO and COD removal efficiencies of 68, 65, and 60% were obtained for EO/UV, EO/Fe(II), and EO/US processes, respectively. The best COD, TOC, and color removal efficiencies were attained for EO/UV/Fe(II) process being 80, 69, and 91%, respectively. The average oxidation state (AOS) and biodegradability index (BI) of the raw and treated samples by various methods were evaluated and the best promising results were obtained for EO/UV/Fe(II) process which were 1.1 and 0.52 for AOS and BI respectively. Additionally, Zahn-Wellens test was conducted and sample treated by EO/UV/Fe(II) was superior to samples treated by other methods, and in just 5 days, minimum biodegradability extent of 70% was met and finally reached over 95% which is an extraordinary result. Finally, the toxicity of the effluent was markedly reduced after sequential processes.
Keywords: Petrochemical wastewater; Electrooxidation; Biodegradability; Zahn-Wellens; UV irradiation; DEGRADATION; DISINFECTION; REMOVAL; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources